2016
DOI: 10.1139/cjps-2016-0221
|View full text |Cite
|
Sign up to set email alerts
|

Postemergence herbicides for control of glyphosate-resistant Canada fleabane in corn

Abstract: Post-emergence herbicides were evaluated for glyphosate-resistant Canada fleabane control in corn (Zea mays L.) from 2013 to 2015. By 8 wk after treatment, dicamba/atrazine (96% control), dicamba (95% control), bromoxynil + atrazine (93% control), dicamba/diflufenzopyr (90% control), and tembotrione/thiencarbazonemethyl + dicamba (85% control) reduced population density and aboveground biomass to levels equivalent to the weed-free control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 8 publications
3
16
1
Order By: Relevance
“…E. Walker], a weed species closely related to horseweed, utilizing several rates of the mix halauxifen-methyl+diclosulam resulted in 80% to 100% control 45 DAT depending on rate and weed height. Other researchers have shown similar results for GR horseweed control with preplant burndown applications of 2,4-D and dicamba (Brown et al 2016; Byker et al 2013; Kruger et al 2010a; Mahoney et al 2017; Mithila et al 2011; Montgomery et al 2017).…”
Section: Resultsmentioning
confidence: 57%
“…E. Walker], a weed species closely related to horseweed, utilizing several rates of the mix halauxifen-methyl+diclosulam resulted in 80% to 100% control 45 DAT depending on rate and weed height. Other researchers have shown similar results for GR horseweed control with preplant burndown applications of 2,4-D and dicamba (Brown et al 2016; Byker et al 2013; Kruger et al 2010a; Mahoney et al 2017; Mithila et al 2011; Montgomery et al 2017).…”
Section: Resultsmentioning
confidence: 57%
“…Other researchers have shown similar results for horseweed control with preplant burndown applications of 2,4-D, dicamba, glyphosate, glufosinate, and saflufenacil (Brown et al 2016;Byker et al 2013;Davis et al 2010;Eubank et al 2008;Kruger et al 2010;Mahoney et al 2017;Mellendorf et al 2013;Mithila et al 2011;Montgomery et al 2017;Owen et al 2009;Shrestha et al 2007;Steckel et al 2006;VanGessel et al 2009). Orthogonal contrasts were used to further compare herbicide treatments ( Table 5) and showed that adding glyphosate, 2,4-D, or dicamba to halauxifen-methyl did not significantly increase GR horseweed control compared to halauxifen-methyl alone.…”
Section: Resultsmentioning
confidence: 67%
“…Other researchers have shown similar results for horseweed control with preplant burndown applications of 2,4-D, dicamba, glyphosate, glufosinate, and saflufenacil (Brown et al 2016; Byker et al 2013; Davis et al 2010; Eubank et al 2008; Kruger et al 2010; Mahoney et al 2017; Mellendorf et al 2013; Mithila et al 2011; Montgomery et al 2017; Owen et al 2009; Shrestha et al 2007; Steckel et al 2006; VanGessel et al 2009).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…A common management strategy implemented by growers for control of GR horseweed is the use of herbicides with alternative modes of action (Scott and VanGessel 2007). In Ontario, several soil-applied residual herbicides controlled GR horseweed >90% in corn (Brown et al 2016;Ford et al 2014); however, POST applied herbicide options for control of multiple-resistant (MR) biotypes in corn are limited (Mahoney et al 2017). In Ontario studies, only dicamba, dicamba:diflufenzopyr, dicamba:atrazine, and bromoxynil þ atrazine applied POST provided >90% control of this species in corn, representing just four herbicide sites of action (Mahoney et al 2017).…”
Section: Introductionmentioning
confidence: 99%